Evoking and Measuring Identification with Narrative Characters – A Linguistic Cues Framework - van Krieken, Kobie; Hoeken, Hans; Sanders, José (Frontiers in Psychology, 2017)
Current research on identification with narrative characters poses two problems. First, although identification is seen as a dynamic process of which the intensity varies during reading, it is usually measured by means of post-reading questionnaires containing self-report items. Second, it is not clear which linguistic characteristics evoke identification. The present paper proposes that an interdisciplinary framework allows for more precise manipulations and measurements of identification, which will ultimately advance our understanding of the antecedents and nature of this process. The central hypothesis of our Linguistic Cues Framework is that identification with a narrative character is a multidimensional experience for which different dimensions are evoked by different linguistic cues. The first part of the paper presents a literature review on identification, resulting in a renewed conceptualization of identification which distinguishes six dimensions: a spatiotemporal, a perceptual, a cognitive, a moral, an emotional, and an embodied dimension. The second part argues that each of these dimensions is influenced by specific linguistic cues which represent various aspects of the narrative character’s perspective. The proposed relations between linguistic cues and identification dimensions are specified in six propositions. The third part discusses what psychological and neurocognitive methods enable the measurement of the various identification dimensions in order to test the propositions. By establishing explicit connections between the linguistic characteristics of narratives and readers’ physical, psychological, and neurocognitive responses to narratives, this paper develops a research agenda for future empirical research on identification with narrative characters.